1998
DOI: 10.1159/000022010
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Gastric Mucosal Repair and Proliferative Activities in Rats Exposed Acutely to Aspirin

Abstract: The present study was designed to determine whether there are any age-related changes in the repair of acute gastric mucosal injury induced by aspirin in Fischer 344 rats. We have also examined the influence of aging on gastric mucosal proliferative activities, a major component of gastric mucosal defense and repair mechanisms. Our data demonstrated that aging was associated with significant delays in both resolution of gross mucosal injury and regeneration of the injured gastric mucosa. However, there were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Neutrophil infiltration into the injured mucosa has been shown to occur as early as 15 to 30 minutes after indomethacin administration in rats 39. In addition, when mucosal damage and repair observed at 3 and 24 hours after aspirin administration were compared, less damage and higher regeneration was found at 24 hours than at 3 hours 16. Thus, mucosal damage at the 24 hour-incubation in the present study might have been sustained after direct damage by NSAIDs instead of cPLA 2 -neutrophil pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil infiltration into the injured mucosa has been shown to occur as early as 15 to 30 minutes after indomethacin administration in rats 39. In addition, when mucosal damage and repair observed at 3 and 24 hours after aspirin administration were compared, less damage and higher regeneration was found at 24 hours than at 3 hours 16. Thus, mucosal damage at the 24 hour-incubation in the present study might have been sustained after direct damage by NSAIDs instead of cPLA 2 -neutrophil pathway.…”
Section: Discussionmentioning
confidence: 99%
“…aging; gastric endothelial cells; angiogenesis; hypoxia; VEGF; importin-␣; hypoxia-inducible factor-1␣ CLINICAL AND EXPERIMENTAL studies indicate that gastric mucosa of aging individuals (referred to herein as aging gastric mucosa or aging gastropathy) has impaired mucosal defense, e.g., reduced prostaglandin generation, decreased mucus and bicarbonate secretion, and an impaired sensory nerve response to luminal acid (6,8,14,24,26,30,32,37,38,40). Not surprisingly, aging gastric mucosa has increased susceptibility to injury by damaging agents including nonsteroidal antiinflammatory drugs (NSAIDs) and ethanol (25,29,30,33).…”
mentioning
confidence: 99%
“…Our previous study identified specific cellular and molecular abnormalities in aging gastric mucosa: hypoxia, increased expression of phosphatase and tensin homolog deleted on chromosome 10, activation of caspases -3 and -9, and reduced expression of survivin that increase susceptibility of the gastric mucosa to injury (35). Aging gastric mucosa also exhibits impaired healing of both acute injury and chronic gastric ulcers (12,26,32,36,37) and reduced therapeutic efficacy of ulcerhealing drugs, including H2 receptor antagonists and protonpump inhibitors (18).…”
mentioning
confidence: 99%
“…The older stomach is also less able to repair itself after damage (Lee et al 1998; Liu et al 1998), which when taken with the antithrombotic effects of aspirin may account for gastrointestinal side effects. Control of the repair processes is poorly understood but does have the potential to be manipulated (Majumdar et al 1997).…”
Section: Developing Strategies To Improve Tolerability Of Aspirinmentioning
confidence: 99%